Assessment of neuroinflammation in patients with idiopathic rapid-eye-movement sleep behaviour disorder: a case-control study. Issue 10 (October 2017) - Stokholm, Morten Gersel; Iranzo, Alex; Østergaard, Karen; Serradell, Mónica; Otto, Marit; Svendsen, Kristina Bacher; Garrido, Alicia; Vilas, Dolores; Borghammer, Per; Santamaria, Joan; Møller, Arne; Gaig, Carles; et al.
Summary: Background: Findings from longitudinal follow-up studies in patients with idiopathic rapid-eye-movement sleep behaviour disorder (IRBD) have shown that most patients will eventually develop the synucleinopathies Parkinson's disease, dementia with Lewy bodies, or multiple system atrophy. Neuroinflammation in the form of microglial activation is present in synucleinopathies and is a potential therapeutic target to halt or delay the neurodegenerative process. We aimed to investigate whether neuroinflammation is present in patients with IRBD and its possible relation to nigrostriatal dopamine function. Methods: In this prospective, case-control, PET study, patients with IRBD and no clinical evidence of parkinsonism and cognitive impairment were recruited from tertiary sleep centres in Spain (Barcelona) and Denmark (Aarhus). We included patients with polysomnography-confirmed IRBD according to established criteria. Healthy controls were recruited through newspaper advertisements. Controls had no motor or cognitive complaints, a normal neurological examination, and a mean group age similar to the IRBD group. In patients with IRBD, we assessed microglial activation in the substantia nigra, putamen, and caudate with 11 C-PK11195 PET, and dopaminergic axon terminal function in the putamen and caudate with 18 F-DOPA PET. Controls underwent either 11 C-PK11195 PET or 18 F-DOPA PET. We compared 18 F-DOPA uptake and 11 C-PK11195 binding potential between groups with an unpaired, two-tailed Student's t test. Findings: Between March 23, 2015, and Oct 19, 2016, we recruited 20 consecutive patients with IRBD and 19 healthy controls. 11 C-PK11195 binding was increased on the left side of the substantia nigra in patients with IRBD compared with controls (Student's t test, mean difference 0·153 [95% CI 0·055 to 0·250], p=0·003), but not on the right side (0·121 [–0·007 to 0·250], p=0·064). 11 C-PK11195 binding was not significantly increased in the putamen and caudate of patients with IRBD. 18 F-DOPA uptake was reduced in IRBD in the left putamen (–0·0032 [–0·0044 to −0·0021], p<0·0001) and right putamen (–0·0032 [–0·0044 to −0·0020], p<0·0001), but not in the caudate. Interpretation: In patients with IRBD, increased microglial activation was detected by PET in the substantia nigra along with reduced dopaminergic function in the putamen. Further studies, including more participants than were in this study and longitudinal follow-up, are needed to support our findings and evaluate whether the presence of activated microglia in patients with IRBD represents a marker of short-term conversion to a clinically defined synucleinopathy in the near future. Funding: Danish Council for Independent Research, Instituto de Salud Carlos III (Spain).